Impact of Push and Pull Factors on Domestic Tourism Motivation in Nepal - Goet, Joginder (Management Dynamics, 2021)
This study aims to investigate the link between push and pull variables and domestic travel motivation, as well as the effects of these elements. The research has used primary sources of data. A well-structured questionnaire was designed to collect data from 260 respondents. The convenience sampling technique was used to select a sample for the study. Moreover, Cronbach's Alpha was assessed to test reliability. The correlational and casual research designs were used. The findings revealed a positive and significant relationship between push and pull factors and domestic tourism motivation and push and pull factors have a significant impact on domestic tourism motivation. This study is useful for those travel owners and managers who want to grab markets. This research suggests a model that enhances push and pull factors through domestic tourism motivation in Nepal.